2007
DOI: 10.1002/ajmg.b.30646
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for association between genetic variants of p75 neurotrophin receptor (p75NTR) gene and antidepressant treatment response in chinese major depressive disorder

Abstract: The p75 neurotrophin receptor (p75(NTR)) is an essential component of neurotrophin system, and has been implicated in the pathogenesis of major depressive disorder (MDD) and in the mechanism of antidepressant action. This study aimed to delineate the association between phenotype (MDD susceptibility and antidepressant response) and genotype (p75(NTR) common genetic variants) in a Chinese population. A total of 228 MDD patients and 402 unrelated controls were recruited. Subjects took selective serotonin reuptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Evidence in support of this hypothesis has been reported (e.g. DTN-BP1 and NGFR ) [16,17] . Therefore, although NR1D1 was not found to play a major key role in the pathophysiology of mood disorders [3] , we considered that NR1D1 might be a susceptibility gene for SSRI treatment response.…”
supporting
confidence: 61%
“…Evidence in support of this hypothesis has been reported (e.g. DTN-BP1 and NGFR ) [16,17] . Therefore, although NR1D1 was not found to play a major key role in the pathophysiology of mood disorders [3] , we considered that NR1D1 might be a susceptibility gene for SSRI treatment response.…”
supporting
confidence: 61%
“…As mentioned earlier, Gau et al (2008) failed to replicate the finding and discussed that the inconsistency of these results could be attributed from the intrinsic difference in the MDD subgroups and different ethnic groups. With respect to Ser205Leu, individual studies contained 164-670 patients with MDD and 164-1130 controls, and the combined sample consisted of 1060 patients and 1688 controls ( Table 2).…”
Section: Discussionmentioning
confidence: 86%
“…However, a subsequent study in a Han Chinese population failed to obtain evidence for the association. 7 This study tried to replicate the association in an independent larger sample. 8 on the basis of unstructured interviews and information from medical records.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should consider genes in the BDNF signaling pathway, which may contribute or interact with BDNF in the response to antidepressant treatment. Recently, we found that one p75NTR missense polymorphism (S250L) was associated with the antidepressant response,53 and TrkB genetic variants may interact with the BDNF Val66Met polymorphism to contribute to the risk of geriatric depression 54. We also found that SNPs in glycogen synthase kinase-3beta ( GSK3B ), an important component in BDNF signaling, were associated with the therapeutic effects of antidepressants 55.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%